RESPONSES OF BRAIN TISSUES AGAINST HYPOXIC CONDITION IN HEMORRHAGIC STROKE PATIENTS: NEUROGLOBIN EXPRESSION IN BRAIN TISSUE AND PLASMA - Mudjihartini, Ninik; LASMA NURHAYATI,; MOHAMAD SAEKHU,; SRI WIDIA A JUSMAN,; JAN PURBA,; MOHAMAD SADIKIN, (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Strokes remain a significant health concern and are the highest cause of mortality and physical or mental disability in productive and the elderly hospitalized patients in Indonesia. Neuroglobin (Ngb) mostly located in the central and peripheral nervous system, predicted enhanced neuronal survival under hypoxic condition, such as in a stroke. The aim of this study is to observe the response of the brain tissue of hemorrhagic stroke patients against hypoxic/ischemic conditions. The objectives are to recognize the pattern of Ngb expression in the brain tissue and plasma of hemorrhagic stroke patients, and furthermore, to compare the level of Ngb in the brain tissue and plasma of hemorrhagic stroke patients. Methods: This is an observational study with consecutive sampling methods using cerebral cortex and the blood of hemorrhagic stroke patients, who underwent craniotomies to evacuate hematomas at Cipto Mangunkusumo Hospital (RSCM) and other hospitals in Jakarta. Ngb expression was measured in brain tissue and blood using real time reverse transcription polymerase chain reaction, while the ELISA method was adopted to measure Ngb protein in plasma. Results: Hypoxia/ischemia in the brain tissue of hemorrhagic stroke patients increased the expression of Ngb in brain tissue compared to the blood. The level of Ngb protein in plasma of hemorrhagic stroke patients increased significantly compared to normal subjects; however, there is no significant difference between the plasma and brain tissue of hemorrhagic stroke patients. Conclusion: Hypoxia/ischemia in hemorrhagic stroke patients increases the expression of Ngb mRNA and protein level. Keywords: Neuroglobin, Hypoxia, Hemorrhagic stroke.